2009
DOI: 10.3390/molecules14010279
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Agelasine D and Analogs for Inhibitory Activity against Pathogenic Protozoa; Identification of Hits for Visceral Leishmaniasis and Chagas Disease

Abstract: There is an urgent need for novel and improved drugs against several tropical diseases caused by protozoa. The marine sponge (Agelas sp.) metabolite agelasine D, as well as other agelasine analogs and related structures were screened for inhibitory activity against Plasmodium falciparum, Leishmania infantum, Trypanosoma brucei and T. cruzi, as well as for toxicity against MRC-5 fibroblast cells. Many compounds displayed high general toxicity towards both the protozoa and MRC-5 cells. However, two compounds exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…These compounds have gained attention because of their biological activity to confer cytotoxicity towards cancer cell lines (minimal inhibitory concentrations of ca. 1 μM; for review see [45]), as well as their anti-bacterial, anti-fungal and anti-protozoal properties [46][47][48][49]. New analogues have been synthesized with activities against Mycobacterium tuberculosis , protozoa such as Plasmodium falciparum and Leishmania infantum as well as against drug-resistant cancer cell lines [50].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have gained attention because of their biological activity to confer cytotoxicity towards cancer cell lines (minimal inhibitory concentrations of ca. 1 μM; for review see [45]), as well as their anti-bacterial, anti-fungal and anti-protozoal properties [46][47][48][49]. New analogues have been synthesized with activities against Mycobacterium tuberculosis , protozoa such as Plasmodium falciparum and Leishmania infantum as well as against drug-resistant cancer cell lines [50].…”
Section: Discussionmentioning
confidence: 99%
“…Vik and colleagues completed a comprehensive screening of agelasine terpene analogs from a marine sponge Agelas sp. and reported that four agelasine analogs ( 65 – 68 ) potently inhibited Leishmania infantum , T. brucei brucei and T. cruzi (IC 50 = 0.093–0.11; 0.11–0.23; 0.11–0.43 μg/mL, respectively) with low concomitant cytotoxicity, suggesting they could become novel leads for design of “potent and selective drugs” [74]. Sanchez and colleagues found two novel linear lipopeptides, almiramides B and C ( 69 , 70 ), from the marine cyanobacterium Lyngbya majuscula that inhibited the protozoan parasite Leishmania donovani (IC 50 = 1.9–2.4 μM) with minimal cytotoxicity towards Vero cells (IC 50 = 33.1–52.3 μM) [75].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Although the effects of other marine compounds, such as agelasine D (Vik et al, 2009), bromopyrrole alkaloids (Scala et al, 2010) and terpenoids (Orhan et al, 2010) on the growth of T. cruzi parasites have already been studied, this is the first study that reports the effects of a protease inhibitor from marine organisms on T. cruzi proteases and how this inhibition may affect the viability of this protozoa. The assays of T. cruzi viability using MTT as a marker was performed incubating epimastigote and metacyclic trypomastigote forms with the inhibitor ShPI-I at 1 × 10 −5 , 1 × 10 −6 and 1 × 10 −7 M for 2, 4, 8, 16, 24 and 48 h (Fig.…”
Section: Effect Of Inhibitor On Viability Assaysmentioning
confidence: 99%